2017
DOI: 10.4103/0259-1162.200225
|View full text |Cite
|
Sign up to set email alerts
|

Perineural nalbuphine in ambulatory upper limb surgery: A comparison of effects of levobupivacaine with and without nalbuphine as adjuvant in supraclavicular brachial plexus block – A prospective, double-blinded, randomizedcontrolled study

Abstract: Background and Aims:Various opioid additives have been trialed to prolong brachial plexus block. We evaluated the effect of adding nalbuphine hydrochloride to levobupivacaine for supraclavicular brachial plexus blockade. The primary end-points were the onset and duration of sensory and motor blocks and duration of analgesia.Materials and Methods:Seventy-eight patients (aged 25–45 years) posted for ambulatory forearm and hand surgery under supraclavicular brachial plexus block were divided into two equal groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Similar results were also reported by Chatrath et al ( 14 ). On the other hand, postoperative tramadol consumptions were significantly lowered in PVD (35 ± 5.3 mg) and PVN (22.5 ± 7.7 mg) than PVB (75 ± 7.2 mg) in the first 24 hours, which was in agreement with Mohamed et al ( 5 ), Mohta et al ( 25 ) and Das et al ( 29 ) findings. Our study revealed that total tramadol consumption was lower in PBN group than in PBD group with no statistical significance, which may be due to the analgesic effect of nalbuphine.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were also reported by Chatrath et al ( 14 ). On the other hand, postoperative tramadol consumptions were significantly lowered in PVD (35 ± 5.3 mg) and PVN (22.5 ± 7.7 mg) than PVB (75 ± 7.2 mg) in the first 24 hours, which was in agreement with Mohamed et al ( 5 ), Mohta et al ( 25 ) and Das et al ( 29 ) findings. Our study revealed that total tramadol consumption was lower in PBN group than in PBD group with no statistical significance, which may be due to the analgesic effect of nalbuphine.…”
Section: Discussionsupporting
confidence: 90%
“…Das et al showed that the nalbuphine group required less amount of diclofenac sodium injection as rescue analgesics with lesser pain scores than patients in the control group in the first 24 hours of the postoperative period. 20 Chiruvella stable in both the groups during the intraoperative and postoperative period as assessed by mean heart rate and mean arterial pressure (MAP) (Fig. 2).…”
Section: Resultsmentioning
confidence: 93%
“…Dose of levobupivacaine was selected from previous studies. [ 7 ] We had selected a slightly lesser dose of drug to be on a safer side. Ambi et al .…”
Section: Discussionmentioning
confidence: 99%